Stateczność i Wytrzymałość Prostokątnego Obramowanego Arkusza Blachy Falistej - Wituszyński, K. (Engineering Transactions, 1957)
The stability and strength of a framed corrugated steel sheet is discussed on examples of bulkheads, subjected to bending, of merchant ships. Since there are various opinions as to the advantages and draw-backs of corrugated and flat (that is welded or riveted) bulkheads, this a paper constitutes a study, from the point of view of strength and stability, of the characteristic features of the «work» of a bent bulkhead subjected also to shear and tensile or compressive load. The material may be divided into three parts: (1) the determination of the resultant direction of oblique tensions above the limit state, (2) the determination of the values of limit stresses for the load considered, and (3) additional considerations concerning the preservation of continuity of horizontal components of oblique tensions along the height of a framed steel sheet or bulkhead. In the first part, relations are established between the resultant direction of oblique tensions and the variable values of stresses. An analysis of the equilibrium of an element makes it possible to conclude that the real direction of oblique tensions is variable with the height. In the second part, limit stresses are calculated by means of the energy method, assuming a probable form of bulkhead deflection under the action of load. In the third part, the energy method is used to investigate the range of distribution of horizontal components of oblique tensions in relation to bulkhead height. An analysis of basic quantities characterizing the «work» of the joint under consideration leads to the conclusion that there is no more than a limited possibility of the bulkhead withstanding the transverse deformations of the ship. The existence of considerable vertical compressive forces, in addition to lowering the limit values of stresses, results in the direction of oblique tensions being nearer to the horizontal position, thus approaching the direction of maximum deformability of the corrugated bulkhead. In view of the influence of the bulkhead on the ship’s hull, it may be replaced by a suitably dimensioned frame which is not a particularly rigid structural element, especially in the neighbourhood of large hatchways.